Cardiac involvement in female Duchenne and Becker muscular dystrophy carriers in comparison to their first-degree male relatives: a comparative cardiovascular magnetic resonance study. (25th June 2015) - Florian, Anca; Rösch, Sabine; Bietenbeck, Michael; Engelen, Markus; Stypmann, Jörg; Waltenberger, Johannes; Sechtem, Udo; Yilmaz, Ali
Abstract: Aims: Duchenne (DMD) and Becker (BMD) muscular dystrophies are X-linked recessive disorders associated with both skeletal myopathy and progressive cardiomyopathy in males. Female DMD/BMD carriers (DMDc/BMDc) are mostly free of skeletal muscle symptoms, but they are also prone to cardiomyopathy. The aim of the current study was to characterize the frequency, pattern, and extent of cardiomyopathy in female DMD/BMD carriers (DMDc/BMDc) in comparison to their first-degree male MD relatives. Methods and results: Thirty-six (age 44 ± 14 years) female MD carriers (20 DMDc and 16 BMDc) constituted the 'MD carrier group' and were prospectively enrolled. All MD carriers underwent a complete CMR study comprising cine- and late gadolinium enhancement (LGE) imaging. In 22 of these women ('female MD carrier comparison group', 7 DMD and 15 BMD), at least one first-degree male relative with a previously established diagnosis of MD underwent the same CMR protocol and was assigned to the 'male MD comparison group' ( n = 24, 6 DMD and 18 BMD). In the total MD carrier group, 17 (47%) MD carriers had at least one pathological CMR finding [5 (14%) with a reduced left ventricular ejection fraction (LV-EF) and 16 (44%) with the presence of LGE]. All LGE-positive patients ( n = 16) showed non-ischaemic LGE with subepicardial involvement of the LV lateral free wall being the most frequent pattern (13/16, 81%). Compared with BMDc, DMDc demonstrated more frequently a pathological CMR result (65 vs. 19%; P = 0.008)—in spite of being significantly younger (40 ± 11 vs. 50 ± 16 years, P = 0.038). In the male MD comparison group, the same LGE pattern as in female carriers was seen, but with a significantly higher prevalence of cardiac abnormalities compared with their female carrier relatives constituting the female MD comparison group (75 vs. 27%; P = 0.003). Conclusion: Cardiac involvement is a frequent finding in female carriers of DMD, but less frequently observed in carriers of BMD. Those DMDc and BMDc with cardiac involvement demonstrate the same myocardial fibrosis pattern as their male counterparts with overt disease.